Estimating Islamic Banks’ Technical and Allocative Inefficiencies: A Shadow Cost Approach - Ouertani, M. N.; Hamdani, H.; Bashir, M. S. (Universiti Sains Islam Malaysia, 2024)
The main objective of the present paper is to empirically analyze the efficiency of 26 selected Islamic banks from different countries, namely: Bahrain, Jordan, Kuwait, Malaysia, Pakistan, Qatar, Saudi Arabia and UAE. The data used covers the period of 2012‒2016. To measure the banks’ efficiency, we used the frontier-based efficiency methodology, which was especially developed in the presence of panel data. In this respect, the panel data provided us with a fruitful framework for analyzing the efficiency. Therefore, the method employed was the shadow cost frontier based on the estimation of parametric cost inefficiency and its decomposition into both technical and allocative inefficiencies. The findings showed that the Islamic banks are costinefficient. With regard to the allocative inefficiency, it can be explained by excessive use of capital relative to labor, accompanied by an overuse of financial resources in terms of labor. The present study also revealed that the financial factor is overused, relative to the physical capital. Furthermore, technical inefficiency appears to be the second source of cost inefficiency as far as the Islamic banks are concerned. Overall, the findings indicate that the Islamic banks must improve their use of resources by about 43.7 percent for achieving efficiency.